Triplet state harvesting and search for forbidden transition intensity in the nitrogen molecule - Minaev, B F.; Panchenko, O O.; Minaeva, V A.; Ågren, H (Frontiers in Chemistry, 2022)
Triplet excited states of the N2 molecule play an important role in electric discharges through air or liquid nitrogen accompanied by various afterglows. In the rarefied upper atmosphere, they produce aurora borealis and participate in other energy-transfer processes connected with atmospheric photochemistry and nightglow. In this work, we present spin–orbit coupling calculations of the intensity of various forbidden transitions, including the prediction of the electric dipole transition moment of the new 13Σg−← A3Σu+ band, which is strongly prohibited by the (+|−) selection rule, the new spin-induced magnetic B′3Σu−← A3Σu+ transition, magnetic and electric quadrupole transitions for the B3Πg← X1Σg+ Wilkinson band, and the Lyman–Birge–Hopfield a1Πg ← X1Σg transition. Also, two other far-UV singlet–singlet quadrupole transitions are calculated for the first time, namely, the Dressler–Lutz a"1Σg+–X1Σg+ and the less studied z1Δg–X1Σg+ weak transitions.